CEO incentives and earnings management - Bergstresser, Daniel; Philippon, Thomas (Journal of Financial Economics, 2006)
Abtract We provide evidence that the use of discretionary accruals to manipulate reported earnings is more pronounced at firms where the CEO's potential total compensation is more closely tied to the value of stock and option holdings. In addition, during years of high accruals, CEOs exercise unusually large numbers of options and CEOs and other insiders sell large quantities of shares.